DIPG-34. PRECLINICAL PRECISION TESTING OF PNOC003 BIOPSY DERIVED MODELS OF DIPG - Panditharatna, Eshini (Neuro Oncol, 2019)
RATIONALE: One of the major hurdles in developing effective treatment for children with DIPG includes the lack of extensive combinatorial studies targeting major driver oncogenic pathways. Combination of H3K27M and TP53 mutations are found in over 50% of DIPG tumors, however, there is a lack of effective combinatorial precision therapy. METHODS: Tissue specimens obtained from subjects with DIPG were used to generate preclinical models. Subjects were enrolled in a prospective molecular diagnostic clinical trial and specimens were obtained by surgical biopsy both at initial diagnosis, and at the time of progression. RESULTS: Fourteen primary neurosphere cell lines and nine xenograft mouse models were successfully generated. The success rate of generating primary neurospheres and xenograft models was 45% and 75%, respectively. Among the 14 cell lines, one was derived from a biopsy performed after tumor progression, and one from washing a biopsy needle. Whole genome analysis of three biopsy-derived primary neurospheres revealed that these samples shared genomic alterations when compared to the primary tumors. All cell lines retained major oncogenic driver mutations in genes such as H3F3A, HIST1H3B, TP53, PPM1D, PIK3R1, and ACVR1. The needle-wash derived cell line was immortalized with hTERT, and exhibited the most deviation in mutation profiles and copy number alterations compared to primary tumor. Global DNA methylation profiling of seven primary tumor biopsies and matched primary neurospheres revealed similar epigenetic profiles. Primary neurospheres derived from biopsies were treated with the same specialized panel of agents recommended by a personalized medicine tumor board, which was based on the mutational profiles of the original tumor. SIGNIFICANCE: All cell lines exhibited varying levels of sensitivity to single agent indicating patterns of intertumor heterogeneity. The use of these model systems allows testing of combinatorial precision therapy for patients with DIPG, where there is a need for rapid translation into clinical trials.